Pengaruh Disiplin Kerja dan Lingkungan Kerja Fisik terhadap Kinerja Guru Pegawai Negeri Sipil (PNS) SMA Negeri 1 XY - Rizkya Syakhira AR; Mochamad Vrans Romi (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to determine the effect of work discipline and the physical work environment on the performance of civil servant (PNS) teachers at SMA Negeri 1 XY. The research method used was quantitative with a positivist approach, involving 30 civil servant teachers as the population. Data were collected through observation, documentation, and questionnaires. Data were analyzed using multiple linear regression. The results showed that partially, work discipline had a significant positive effect on teacher performance, and the physical work environment also had a significant positive effect on teacher performance. Simultaneously, work discipline and the physical work environment had a very significant effect on the performance of civil servant teachers at SMA Negeri 1 XY. The conclusion of this study is that improving work discipline and improving the physical work environment can optimally improve teacher performance.   Keywords: Work Discipline, Physical Work Environment, Teacher Performance